Masalah Sosial Dalam Kalangan Pelajar Dan Hubungannya Dengan Pembentukan Karakter Pelajar - Muhammad Isa; Aulia Rahman; Sutrisno, Imam Hadi; Mufti Riyati (Program Studi Pendidikan Sejarah - Universitas Samudra, 2025)
This study discusses the things that influence students to be involved in juvenile delinquency. The increasingly serious social problems that are spreading have even become commonplace even in the world of education. Education that is able to shape children's character is not limited to formal educational institutions, but also in non-formal education such as family and society. This study aims to determine the achievement of students' character in dealing with social problems. By using a quantitative descriptive method involving 30 students from SMK Negeri 1 Kota Langsa. From the results of the analysis, only family factors are not the main cause of student involvement in social problems. In addition, the main causes of student involvement in social problems are personal factors, between friends and the environment. This study concludes that students need to be equipped with Social Science. This science has educational materials from the disciplines of social sciences and humanity (educational science and history) which are presented scientifically and psychologically with educational goals based on Pancasila and Indonesian Culture. All parties must work together to eliminate this increasing social problem. Schools can supervise students more while at school so that they do not commit juvenile delinquency, parents must also guide and always advise their children to always do positive activities and instill religious values ​​in their children so that children have a strong foundation. And society must also care about each other and dare to reprimand if there are teenagers who do deviant behavior.